Hospital Health Promotion Program Influence on Stroke Patients’ Motivation for Medical Rehabilitation (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2023)
Stroke is the second leading cause of death and the third leading cause of disability. World Health Organization in 2021 found that around 70% of disability and 87% of deaths due to stroke occur in low- and middle-income countries. One of Indonesia’s efforts to minimize disability in post-stroke patients is medical rehabilitation. In an effort to maintain the patients’ motivation to adhere to medical rehabilitation, hospitals employ the hospital health promotion program. The purpose of this study is to analyze the effect of the hospital health promotion program on stroke patients' motivation for medical rehabilitation. This quantitative analytic study with a cross-sectional approach was conducted at Haji Adam Malik Central General Hospital and Medan Haji General Hospital. The research population was 124 post-stroke patients (48 patients from Haji Adam Malik Central General Hospital and 76 patients from Medan Haji General Hospital) and all of them were used as samples (total sampling). Data collection was conducted using a valid and reliable questionnaire (validity and reliability test carried out). Analysis was carried out using frequency distribution, chi-square, and double-log regression analysis. This study found that 90 out of 124 participants had high motivation for medical rehabilitation, while the rest had low motivation. The results showed that the hospital health promotion program had a significant effect on the motivation of stroke patients for medical rehabilitation, namely empowerment (OR=2.842), atmosphere building (OR=2.937), advocacy (OR=3.028), and partnerships (OR=2.738). Advocacy has the most impact on the patient’s motivation with OR=3.028. It can be concluded that hospital health promotion program has a positive influence on stroke patients’ motivation to undergo medical rehabilitation. Hence, implementation of similar health promotion program on other hospitals are highly encouraged to influence stroke patients’ motivation for medical rehabilitation.